Prospective, randomized, double‐blind assessment of topical bakuchiol and retinol for facial photoageing. (21st September 2018) - Dhaliwal, S.; Rybak, I.; Ellis, S.R.; Notay, M.; Trivedi, M.; Burney, W.; Vaughn, A.R.; Nguyen, M.; Reiter, P.; Bosanac, S.; Yan, H.; Foolad, N.; et al.
Summary: Background: Bakuchiol is a phytochemical that has demonstrated cutaneous antiageing effects when applied topically. Early studies have suggested that bakuchiol is a functional analogue of topical retinoids, as both compounds have been shown to induce similar gene expression in the skin and lead to improvement of cutaneous photodamage. No in vivo studies have compared the two compounds for efficacy and side‐effects. Objectives: To compare the clinical efficacy and side‐effect profiles of bakuchiol and retinol in improving common signs of cutaneous facial ageing. Methods: This was a randomized, double‐blind, 12‐week study in which 44 patients were asked to apply either bakuchiol 0·5% cream twice daily or retinol 0·5% cream daily. A facial photograph and analytical system was used to obtain and analyse high‐resolution photographs of patients at 0, 4, 8 and 12 weeks. Patients also completed tolerability assessment questions to review side‐effects. During study visits, a board‐certified dermatologist, blinded to study group assignments, graded pigmentation and redness. Results: Bakuchiol and retinol both significantly decreased wrinkle surface area and hyperpigmentation, with no statistical difference between the compounds. The retinol users reported more facial skin scaling and stinging. Conclusions: Our study demonstrates that bakuchiol is comparable with retinol in its ability to improve photoageing and is better tolerated than retinol. Bakuchiol is promising as a more tolerable alternative to retinol. Abstract : What's already known about this topic? Bakuchiol is a plant‐derived phytochemical that is known to have retinoid‐like effects in vitro . What does this study add? This clinical study suggests that topical bakuchiol is similar to topical retinol in improving facial wrinkles and pigmentation. Bakuchiol was better tolerated with fewer side‐effects. Linked Comment: Lev‐Tov. Br J Dermatol 2019;180 :253–254 . Plain language summary available online Respond to this article